Effects of Alhagi maurorum and Cardaria draba weeds on mineral nutrients absorption in wheat - Nayer Mohammadkhani; Moslem Servati (فیزیولوژی محیطی گیاهی, 2018)
Allelopathy can affect the plant growth and change the soil nutrient contents. The aim of this study was evaluation of the allelopathic effects of Alhagi maurorum L. and Cardaria draba L. as two important weeds in wheat fields on nutrient absorption of this crop. Pot experiments were designed to study the allelopathic effects of A. maurorum and C. draba shoots on mineral nutrient contents in wheat. The absorption of high demand (NO3-, K+, Ca2+ and P) and low demand micronutrients (Fe2+ and Cu2+) in roots and shoots of wheat plants reduced in plants cultivated on rhizospheric soil of A. maurorum and C. draba. Allelopathy did not affect absorption of Mg2+,  Mn2+, and Zn2+. Allelopathic effect of A. maurorum was significantly (P<0.05) higher than C. draba. It seems that decrease in mineral nutrients absorption was because of allopathic effects of the released allelochemicals from the roots of C. draba and A. maurorum.